2021
DOI: 10.1111/jpn.13575
|View full text |Cite
|
Sign up to set email alerts
|

Health and nutrition of loggerhead sea turtles (Caretta caretta) in the southeastern United States

Abstract: Loggerhead sea turtles (Caretta caretta) are opportunistic carnivores that feed primarily on benthic invertebrates and fish. Sea turtle rehabilitation requires provision of a species‐specific, balanced diet that supplies nutrition similar to that of a wild diet; this can be challenging because free‐ranging loggerheads’ diets vary depending on their life stage and geographic location, with predominant prey species dictated by local availability. The goal of this study was to better understand the nutritional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…for use in isotopic mixing models) do not exist from the study site. Prior studies of gut contents from stranded loggerheads on the Atlantic coast of the southeastern United States indicated that subadults might primarily consume fish before switching to a gastropod-dominated diet as adults [ 91 , 92 ]. However, existing isotopic forage item data from the Gulf of Mexico [ 93 ] suggest that most fishes' δ 15 N is higher (mean = 10.64 ± 2.36 ‰ s.d.)…”
Section: Discussionmentioning
confidence: 99%
“…for use in isotopic mixing models) do not exist from the study site. Prior studies of gut contents from stranded loggerheads on the Atlantic coast of the southeastern United States indicated that subadults might primarily consume fish before switching to a gastropod-dominated diet as adults [ 91 , 92 ]. However, existing isotopic forage item data from the Gulf of Mexico [ 93 ] suggest that most fishes' δ 15 N is higher (mean = 10.64 ± 2.36 ‰ s.d.)…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although the genetic origin of juvenile green turtles captured on the pier is unknown, green turtle nesting has increased exponentially in Florida in recent years (Ceriani et al, 2019) while loggerhead nesting has remained stable (Ceriani et al, 2019) and Kemp’s ridley nesting appears to have declined (Caillouet et al, 2018; Gallaway et al, 2016). Capture of Kemp’s ridleys and loggerheads on recreational fishing piers may not be unexpected considering that the bait typically used by recreational anglers (e.g., fish, shrimp) are known diet items of these species (Molter et al, 2021; Ramirez et al, 2020; Shaver, 1991). However, capture of green turtles on the NAV pier was unexpected as juvenile green turtles in neritic habitats are generally considered herbivores (Williams et al, 2014).…”
Section: Discussionmentioning
confidence: 99%